Teaching Spoken Language Strategy At ELLA (English Learning Area) In Kampung Inggris Pare (Conference on English Language Teaching, 2023)
English has an important role for learners to communicate in their daily life in globalization era and to develop their communication. This study aims to analyze the teachers’ strategy in teaching spoken language and investigate students' speaking performance at ELLA (English Learning Area) in Kampung Inggris Pare. The method of research used is qualitative research which is descriptive design by applying observation, field note, interview, and questionnaire. The result of this research shows that the teachers applied twelve strategies according to freeman (2000), namely translation of a literary passage, deductive application of rule, memorization, reading aloud, question and answer exercise, conversation practice, backward build-up (Expansion) drill, repetition drill, transformation drill, question-answer drill, peer correction, and structured feedback. In addition, based on the theory from Hughes (2002), there are five categories in speaking performance such as accent, grammar, vocabulary, fluency, and comprehension. Which is the average of students’ scores is 81, with a rating of (B+). It indicates that the students’ speaking performance at ELLA (English Learning Area) is very good. Based on the result, it is suggested for the teachers to allow all the students to take active participation in the classroom, to make the students more engaged in classroom activities.